Exploring Risk Perception in the Romanian Covid-19 Pandemic (GeoPatterns, 2025)
Knowing how a crisis is perceived by a population can lead to more optimal and effective measures to combat negative effects of disasters in this context, attitudes, the degree of involvement, the speed of accepting imposed measures, play an important role for a preventive, pro-active behaviour of both individual- and community-level. In this paper, based on the data provided by a quantitative questionnaire applied in two non-sequential waves (177 responses in Wave 1 and 368 responses in Wave 5), some aspects of the five constructs expressing the types of perception towards authorities, support, risk of illness, duration of the COVID-19 pandemic, media and some of the factors that may influence perception (personality, cognitive-attitudinal, emotional, behavioural, demographic aspects) are analysed.
Keywords: psychometric research; Covid-19 perception; behaviour; transversal method